Аналіз напрямків розвитку банківської сфери через управління ІТ проектами - Морозов, Віктор Володимирович; Остахов, Володимир Вікторович (НТУ "ХПІ", 2017)
У статті розглядаються причини й наслідки переформатування бюджетів ІТ проектів в банківських організаціях. Аналізуються та проводяться паралелі у підходах вибору ІТ проектів для впровадження в закордонних та українських фінансових установах. Це суттєво впливає не тільки на результати досліджень та вибору ІТ проектів, але так само на розвиток таких організацій в цілому. Авторами зроблено висновки про тренди впровадження ІТ проектів та їх вплив на розвиток бізнесу банківського сектору.

In this article the causes and consequences of IT projects‘ budgets reformatting in banking organizations are investigated. Analysis and parallels in approaches of choosing IT projects to be implemented in foreign and Ukrainian financial institutions are being conducted. This significantly affects not only the results of investigation and selection of IT projects, but also on the development of such organizations in general. The analysis shows that on the background of global GDP decrease, banks around the world are increasing their IT investments, but investments in IT projects are heavily redistributed towards digital transformation. Nevertheless, IT projects are a major driver of banking business development, so their number is rapidly growing every day in the fields of big data analytics, virtualization and cloud computing, mobility, scoring, target marketing, IT infrastructure etc. The authors draw conclusions about trends in implementation of IT projects and their impact on the development of the banking business sector.
Analysis of the development directions of the banking sector through the management of IT projects
Keywords: ІТ проект; банк; бюджет; система; тренд; IT project; bank; budget; system; trend